Economic Aspects of Assessing the Energy Security of Power Systems in Russian Regions - Evgeny LISIN; Oksana KONOVALOVA; Valery LOZENKO (Communications of International Proceedings, 2020)
The paper examines the problem of assessing the level of Russian regions power systems energy security from the perspective of economic and managerial threats to consumers reliable power supply. A method for determining the economically justified level of energy security of regions in the conditions of market liberalization in the power industry is proposed. The method is based on an optimization criterion for ensuring a balance of interests of territorial government bodies and regional generating companies in the formation of regional energy systems development strategy.
Keywords: Energy security; regional power systems; territorial public administration; regional energy companies; energy markets; economic accessibility; optimization criterion.